Identification and characterization of Pestalotiopsis spp. causing leaf spot and leaf blight on jabon (Neolamarckia spp.) in Indonesia - ELIS NINA HERLIYANA; PRADHIPTA OKTAVIANTO; ULFAH JUNIARTI SIREGAR (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Herliyana EN, Oktavianto P, Siregar UJ. 2022. Identification and characterization of Pestalotiopsis spp. causing leaf spot and leaf blight on jabon (Neolamarckia spp.) in Indonesia. Biodiversitas 23: 6547-6556. Jabon (Neolamarckia spp.) is one of the fast-growing trees with high economic value for industrial plantations. Its monoculture planting system is faced with certain problems, such as the leaf spot and leaf blight diseases caused by Pestalotiopsis sp. Therefore, the aim of this research was to describe the morphology of Pestalotiopsis species through macroscopic and microscopic observations, followed by the identification of fungus using DNA barcoding causing leaf spot and leaf blight on the tree. A total of 11 Pestalotiopsis isolates were used for this research. The morphology was identified by observing mycelium colonies and fungal conidia, while DNA barcoding was initiated after DNA isolation using cetyltrimethylammonium bromide (CTAB) method, amplification with ITS 1 and 4 primers, followed by sequencing process. The results of DNA barcoding showed that 5 species of Pestalotiopsis, namely Pseudopestalotiopsis theae, Pestalotiopsis microspora, Pestalotiopsis palmarum, Neopestalotiopsis clavispora, and Pestalotiopsis virgatula were found associated with leaf spot and blight disease. All the five species were further classified into 3 clades using phylogeny according to their median cells and apical appendage shape. The clade X consisted of P. palmarum, N. clavispora, and P. virgatula with versicolorous median cells, whereas clade Y included P. microspora with concolorous median cell, and clade Z consisted Ps. theae with concolorous median cell and knobbed apical appendage.